Consumer-friendly DRM: the quest for transparency and interoperability in a single European information space (Part 1). (2nd June 2010) - Cartwright, Emma
Love it or hate it, Digital Rights Management (DRM) is here to stay. The European Commission has committed to changing the DRM landscape in its quest for the development of what has been coined the 'fifth freedom' of the single market: the free movement of knowledge and innovation. Many suggest that DRM should be differentiated from 'copy protection mechanisms' which only attempt to prohibit unauthorised copies of media or files, and also from 'technical protection measures' (TPMs) which control and/or restrict the access of digital media content on digital devices with such technologies installed. DRM, on the other hand, controls the usage of content in a more detailed fashion, as DRM systems can determine what can and cannot be done with and to a digital copyright work in single instances. From a legal perspective, the nomenclature used in the European Union (EU) laws and surrounding discussion papers which govern the rules relating to DRM systems are by way of reference to TPMs and copy protections, and this paper will refer to these terms also. This will be a two-part article.